1003 Sleep Spindle Abnormalities In Youth With Ptsd. (27th May 2020) - Peterson, B; Castelnovo, A; Riedner, B; Herringa, R; Jones, S
Abstract: Introduction: Sleep disturbance is central to the phenomenology of PTSD across the lifespan with up to 90% of youth with PTSD reporting sleep disturbance. Subjective sleep dysfunction has also been linked to the development, maintenance and severity of the disorder. However, to date there have been no objective EEG assessments of sleep in youth with PTSD, and little is known about how the disease impacts specific sleep features. Methods: Ten youth with PTSD (aged 14.5±3.2; CAPS-CA score 60.5±25.3) and ten age-and sex-matched typically developing youth (TD) (aged 14.7±3.2) completed two non-consecutive overnight high-density EEG (256-channel) polysomnography sleep studies. Prior to sleep on one night, participants performed an emotion processing task. Group differences in sleep macrostructure variables were assessed with two-way ANOVA, and group differences in all-night spectral density were assessed using unpaired t-tests. An automatic algorithm was used to detect spindle amplitude, duration, and density topographically. Statistical non-parametric mapping (SnPM) cluster testing was used to determine significantly different topographic differences between groups. Results: No significant group differences were observed in sleep macrostructure variables. All-night spectral density analysis revealed increased power in PTSD youth relative to TD youth in the sigma band on both task and baseline nights. PTSD youth showed higher spindle duration, higher integrated spindle activity, and higher spindle amplitude globally both nights relative to TD youth. The increase in spindle duration achieved significance in a robust frontal cluster on both nights (43-channel cluster (p = .044) on baseline night, 66-channel cluster (p = .019) on task night). Conclusion: Structural and functional abnormalities of the prefrontal cortex are a prominent feature of pediatric PTSD. The observed increase in spindle duration may represent another marker of impaired cortical function in youth with PTSD reflecting a failure of cortical inhibition of the thalamically-generated spindle rhythm. Support: K08 MH100267 to RH, Wisconsin Institute for Sleep and Consciousness Pilot Award to SJ